Vampire in the darkness: a new genus and species of land leech exclusively bloodsucking cave-dwelling bats from China (Hirudinda: Arhynchobdellida: Haemadipsidae) - Huang, Taifu; Liu, Zhiwei; Gong, Xiaoyan; Wu, Tao; Liu, Hui; Deng, Jiaxin; Zhang, Youxiang; Peng, Qingzhong; Zhang, Libiao; Liu, Zhixiao (Zootaxa, 2019)
Land leeches in the family Haemadipsidae are mostly from the humid tropical rainforest habitats and habitually take blood from the body of human and other animals. In the present study, we report a new species, Sinospelaeobdella wulingensis sp. n., from caves in the northern subtropical Wuling Mountains of central-south China that feeds blood exclusively on cave-dwelling bats. Based on morphological characteristics, COI gene sequence divergence, and phylogenetic analysis, a new genus Sinospelaeobdella gen. n. is established for the new species, to which a previously described species Haemadipsa cavatuses Yang et al., 2009 is transferred as S. cavatuses comb. n. We also provided extended discussion on phylogenetic relationship within the “Tritetrabdellinae” clade uncovered in a previous study, DNA taxonomy, morphological and behavioral adaptions, biogeography, and possible involvement of Sinospelaeobdella gen. n. in bat transmitted diseases of public concerns.